Soluble urokinase plasminogen activator receptor and decline in kidney function in autosomal dominant polycystic kidney disease - Hayek, Salim; Landsittel, Douglas P.; Wei, Changli; Zeier, Martin; Yu, Alan S. L.; Torres, Vicente E.; Roth, Sharin; Pao, Christina S.; Reiser, Jochen (Journal of the American Society of Nephrology, 2019)
Visual Abstract - Download figureOpen in new tabDownload powerpoint - - Background Levels of soluble urokinase plasminogen activator receptor (suPAR), an inflammation marker, are strongly predictive of incident kidney disease. Patients with autosomal dominant polycystic kidney disease (ADPKD) experience progressive decline in renal function, but rates of decline and outcomes vary greatly. Whether suPAR levels are predictive of declining kidney function in patients with ADPKD is unknown. - Methods We assessed suPAR levels in 649 patients with ADPKD who underwent scheduled follow-up for at least 3 years, with repeated measurements of height-adjusted total kidney volume and creatinine-derived eGFR. We used linear mixed models for repeated measures and Cox proportional hazards to characterize associations between baseline suPAR levels and follow-up eGFR or incident ESRD. - Results The median suPAR level was 2.47 ng/ml and median height-adjusted total kidney volume was 778, whereas mean eGFR was 84 ml/min per 1.73 m2. suPAR levels were associated with height-adjusted total kidney volume (β=0.02; 95% confidence interval, 0.01 to 0.03), independent of age, sex, race, hypertension, and eGFR. Patients in the lowest suPAR tertile (<2.18 ng/ml) had a 6.8% decline in eGFR at 3 years and 22% developed CKD stage 3, whereas those in the highest tertile (suPAR>2.83 ng/ml) had a 19.4% decline in eGFR at 3 years and 68% developed CKD stage 3. suPAR levels >2.82 ng/ml had a 3.38-fold increase in the risk of incident ESRD. - Conclusions suPAR levels were associated with progressive decline in renal function and incident ESRD in patients with ADPKD, and may aid early identification of patients at high risk of disease progression.
Gesehen am 23.07.2020